The economic weapon : the rise of sanctions as a tool of modern war - Mulder, Nicholas (Connecticut, USA ; London : Yale University Press, 2022)
Economic sanctions dominate the landscape of world politics today. First developed in the early twentieth century as a way to use the flows of globalization to defend liberal internationalism, their continuing appeal is that they function as an alternative to war. This view, however, ignores the dark paradox at their core: designed to prevent war, economic sanctions are modeled on devastating techniques of warfare. tracing the use of economic sanctions from the blockades of World War I to the policing of colonial empires and the interwar confrontation with fascism, Nicholas Mulder combines extensive archival research with political, economic, legal, and military history to reveal how a coercive wartime tool was adopted as an instrument of peacekeeping by the League of Nations. This timely study casts an overdue light on why sanctions are widely considered a form of war, and why their unintended consequences are so tremendous.
Includes index.
Includes bibliographical references p. 299-416.
ne 18/08/2022
Loans
Keywords: Economic sanctions; International economic relations; War